A three-dimensional volume of fluid & level set (VOSET) method for incompressible two-phase flow. (2nd September 2015) - Ling, Kong; Li, Zhao-Hui; Sun, Dong-Liang; He, Ya-Ling; Tao, Wen-Quan
Highlights: A simple method is proposed for the implementation of PLIC in three dimensions. A simple method is proposed for the calculation of level-set function in three dimensions. Two techniques are proposed for saving CPU time in computing the distance functions, and the effect is obvious. Numerical results are provided in good agreement with experimental data. Abstract: This paper presents a three-dimensional VOSET method, which combines both advantages of the VOF and level set. The basic idea is the same with that in 2D VOSET, but new methods are proposed to deal with new geometric problems in three dimensions. An iterative root-finding method is used for implementing Piecewise Linear Interface Construction (PLIC) in three dimensions. An iterative geometric method is presented to calculate the level-set function. The feasibility and accuracy of this method are analyzed by some classical test problems. Combining the use of projection method that solves the flow field, the 3D VOSET is adopted to simulate a liquid dam break problem and a single-bubble rising problem. Our numerical results are found to be in good accordance with those in previous studies.